Samuel Beckett's television plays: means of production, literary genres, critical theory (ARS, 2016)
The article raises some questions to a further investigation of Samuel Beckett’s late works, particularly his television plays produced by the Süddeutscher Rundfunk - SDR (today: Südwestrundfunk - SWR) between 1966 and 1985: Eh Joe, Geistertrio, ... Nur noch Gewölk …, Quadrat I & II, Nacht und Träume, Was Wo. It is suggested that the television plays might be approached by the technological development of the means of production as well as by the historicity of artistic genres. Both questions have their theoretical background in the aesthetic reflection of Adorno and Benjamin. From this perspective, the television plays resume the rupture of genres that Beckett was already dealing with in his prose and theatre works by configuring a new means of artistic production during his work with the German public television station